Effects of Supplemental Perioperative Oxygen in Preventing Transient Hypoparathyroidism After Total Thyroidectomy - Mehmood, Sajjid (Cureus, 2018)
Background Thyroidectomy is one of the most common endocrine procedures performed worldwide. Post-operative hypocalcemia is a troublesome complication of thyroid surgery. Few studies have considered the role of supplemental oxygen in preventing postoperative hypocalcemia in patients undergoing thyroidectomy. Materials and methods This was a randomized controlled study comparing the use of high flow supplemental oxygen (FiO(2) 80%) with low flow oxygen (FiO(2) 30%) in preventing transient postoperative hypocalcemia. Seventy-eight patients undergoing thyroidectomy during the year 2017 in Surgery Unit-1, Holy Family Hospital were included in the study. Results Transient hypoparathyroidism was present in 20.5% (n=8/39) in group 1 while it was present in 59.0% (n=23/39) in group 2 patients. Patients in group 1 (FiO(2) 80%) demonstrated a significantly lower percentage of transient hypoparathyroidism than group 2 (FiO(2) 30%) (P=0.001). Conclusion Our study concluded that high flow supplemental oxygen (FiO(2 )80%) significantly decreases the risk of developing postoperative transient hypocalcemia.